FUNGSI AUDITOR DALAM TINJAUAN ETIKA PANCASILA RELEVANSINYA BAGI PELAKSANAAN PENGAWASAN KEUANGAN NEGARA - , Dalibas, SE.,MM., Prof. Dr. Lasiyo, M.A., M.M. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Writing of dissertation entitled: Auditor Function in the Evaluation Pancasila Ethics, Its Relevance for Observation Auditing of State, background by concern of national, namely rampant progressively act badness of corruption which continue gnawed state's finance. One of the commissioned state apparatus to conduct of state's finances is auditor. The strategic auditor function, hence auditor have to have sturdy and tart moral. One of the moral source which need and made as elementary orientation of behaviour all auditors are Five Principles moral